Determinants of Physical Teachers’ Attitude toward Technology Integration in Shenzhen Schools, China - Xu, Jiaoshiyun; Phongsatha, Satha (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aim: This study aimed to identify the factors influencing Physical teachers’ attitudes toward technology integration in Shenzhen Schools, China. The variables used in this research framework include Content Knowledge, Pedagogical Knowledge, Technological Knowledge, Technology Pedagogy and Content Knowledge, Technology Integration Self-efficacy, Intention to Integrate Technology, Teaching Style, Contextual Factors, Intention to Integrate Technology and Instructional Technology Outcome Expectation. Materials and Methods: The research utilized a quantitative survey research method using a questionnaire to investigate the influencing factors. The purposive sampling technique was employed to recruit 359 respondents in Shenzhen City to participate in the study. The Confirmatory Factor Analysis and Structural equation model was utilized to test the hypotheses. Results: The results revealed that physical education teachers’ intention to integrate technology can be influenced by the attitudes of Technological Integration Self-efficacy and Contextual Factors. In addition, the Technology Integration Self-efficacy is influenced by Technological Pedagogical and Content Knowledge. For the instructional technology outcome expectation, this factor can be influenced by the TISE and the IIT. Furthermore, the mediating effects were found for the teachers’ intention to integrate technology and the technology integration self-efficacy. Conclusion: The results showed that for physical education teachers to change their attitude toward technology integration, they need to increase their self-efficacy level. It is also important for the school to provide additional technology knowledge or support for teachers to ensure that the teachers can increase their competency toward technology usage, which could result in the increased utilization of technology in physical education classes.